Leveraging drone technology for enhanced thermal performance analysis in sustainable architecture: a case study of GBI-certified buildings in Malaysia - Abd Manan, Mohd Shahrudin; Abd Halin, Al-Fhaliq Naabil (Taylor and Francis Ltd., 2024)
In recent years, the realm of architecture has witnessed a significant transformation marked by a notable surge in focus on sustainable practices and energy efficiency. Architects and engineers increasingly recognize the innovative role of thermal efficiency in enhancing building performance. Such recognition emphasizes the critical importance of thermal analysis in understanding the thermal attributes of building materials and structures. Against this backdrop, this paper aims to bridge a current gap in architectural practices and sustainable design within the Malaysian context. It proposes a case study leveraging drone thermal mapping techniques on Green Building Index (GBI)-certified buildings. The study seeks to examine how architectural designs interact with environmental conditions and identify areas for improvement in sustainable building practices, particularly within Malaysia’s tropical climate context. The primary objective is to assess the effectiveness of drone technology in analysing building thermal performance and to explore how the findings can inform design interventions to enhance sustainability. To achieve this, a structured methodology comprising five procedural phases is employed in a case study focused on three iconic GBI-certified buildings in Putrajaya, namely Putrajaya Holdings Tower, Energy Commission Building, and Heriot-Watt University Malaysia. By integrating thermal imaging with visuospatial data and 3D modeling techniques, the study demonstrates the effectiveness of drones in analysing heat patterns, highlighting their potential as a tool for strategic design interventions. As an exploratory study, this paper serves as a catalyst for further investigations into the integration of drone technologies with architectural design, particularly within the context of tropical climates.